2018
DOI: 10.1111/1440-1681.12909
|View full text |Cite
|
Sign up to set email alerts
|

Arginase and α‐smooth muscle actin induction after hyperoxic exposure in a mouse model of bronchopulmonary dysplasia

Abstract: The L-arginine/NO pathway is an important regulator of pulmonary hypertension, the leading cause of mortality in patients with the chronic lung disease of prematurity, bronchopulmonary dysplasia. L-arginine can be metabolized by NO synthase (NOS) to form L-citrulline and NO, a potent vasodilator. Alternatively, L-arginine can be metabolized by arginase to form urea and L-ornithine, a precursor to collagen and proline formation important in vascular remodelling. In the current study, we hypothesized that C3H/He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…It is possible that the absence of an increase in arterial α-SMA in hyperoxic pulmonary arteries in our mouse model could explain these discrepancies. However, increased α-SMA associated with vascular smooth muscle thickening in pulmonary arteries of hyperoxic mice was also reported in a study which had applied 85% O 2 (83). We have shown that 85% O 2 represents a more severe model of BPD (19) when compared to the 65% O 2 we applied here; thus, a lower O 2 level could account for the absence of ex vivo vascular reactivity and markers of vascular remodeling in our study.…”
Section: Discussionmentioning
confidence: 53%
“…It is possible that the absence of an increase in arterial α-SMA in hyperoxic pulmonary arteries in our mouse model could explain these discrepancies. However, increased α-SMA associated with vascular smooth muscle thickening in pulmonary arteries of hyperoxic mice was also reported in a study which had applied 85% O 2 (83). We have shown that 85% O 2 represents a more severe model of BPD (19) when compared to the 65% O 2 we applied here; thus, a lower O 2 level could account for the absence of ex vivo vascular reactivity and markers of vascular remodeling in our study.…”
Section: Discussionmentioning
confidence: 53%
“…The products of ODC and OAT play an important role in endothelial and smooth muscle cell proliferation and collagen synthesis, respectively, and therefore are thought to contribute to pathologic vascular remodeling in some forms of PH. 19 , 39 Considering our result that L-citrulline increases arginase activity, we expected an increase in ODC and OAT protein abundance due to the likely increase in the shared substrate and product of arginase activity, L-ornithine. However, we found that ODC and OAT protein levels were not increased at any concentration of L-citrulline that we studied, including concentrations that increased arginase activity in hypoxic PAECs ( Fig.…”
Section: Discussionmentioning
confidence: 94%
“…Collagen I is mainly localized in bronchi, alveolar septa, and blood vessels, and was overexpressed in patients with BPD, resulting in failure of alveolar septation during BPD progression [ 25 ]. According to a recent study, protein levels of α-SMA in lung tissues and blood vessels of BPD mice induced by hyperoxia were far higher than those in normal mice [ 26 ]. These experiments strongly suggest that Xist promotes BPD malignancy.…”
Section: Discussionmentioning
confidence: 99%